Outcome of endoscopic sphincterotomy in post cholecystectomy patients with sphincter of Oddi dysfunction as predicted by manometry and quantitative choledochoscintigraphy. Issue 5 (1st May 2002) - Cicala, M; Habib, F I; Vavassori, P; Pallotta, N; Schillaci, O; Costamagna, G; Guarino, M P L; Scopinaro, F; Fiocca, F; Torsoli, A; Corazziari, E
Abstract : Background: Sphincter of Oddi dysfunction is diagnosed at manometry and, after cholecystectomy, non-invasively at quantitative choledochoscintigraphy. Patients may benefit from endoscopic sphincterotomy. Aims: The aim of this study was to assess the usefulness of choledochoscintigraphy compared with manometry in predicting outcome of sphincterotomy in post cholecystectomy patients with sphincter of Oddi dysfunction. Patients and methods: Thirty patients with biliary-type pain complying with the Rome diagnostic criteria of sphincter of Oddi dysfunction and belonging to biliary group I and II were subjected to clinical evaluation, choledochoscintigraphic assessment of the hepatic hilum-duodenum transit time, endoscopic retrograde cholangiopancreatography, and perendoscopic manometry. Twenty two biliary group I and II patients with prolonged hepatic hilum-duodenum transit times were invited to undergo sphincterotomy. Fourteen patients underwent sphincterotomy; eight refused. Clinical and scintigraphic assessments were performed at follow up. Results: Hepatic hilum-duodenum transit time was delayed in all patients with manometric evidence of sphincter of Oddi dysfunction, in all biliary group I patients and in 64% of biliary group II patients. At follow up, all patients who underwent sphincterotomy were symptom free and hepatic hilum-duodenum transit time had either normalised or significantly improved. A favourable post sphincterotomy outcome was predicted in 93% of cases at choledochoscintigraphy and in 57% at manometry. Conclusions: Quantitative choledochoscintigraphy is a useful and non-invasive test to diagnose sphincter of Oddi dysfunction as well as a reliable predictor of sphincterotomy outcome in post cholecystectomy biliary group I and II patients, irrespective of clinical classification and manometric findings.